P53 and Cellular Glucose Uptake. (July 2013) - de la Torre, Alejandro J.; Rogoff, Daniela; White, Perrin C.
<x xml:space="preserve">Abstract</x> Objectives. Tumor protein p53 is a transcription factor involved with cellular responses to stressors including limited glucose availability. We hypothesized that modulating p53 levels would affect cellular glucose uptake. Methods and Results. Transfecting cultured primary mouse hepatocytes with p53 siRNA suppressed p53 mRNA expression >90%. Control hepatocytes (transfected with non-targeting siRNA) increased glucose uptake (2.28 ± 1.02-fold vs basal, p 0.009) in response to 100 nM insulin, but p53 siRNA-treated hepatocytes had a blunted response (0.92 ± 0.11-fold vs basal; between group difference p 0.0012). In adipocytes differentiated from the pre-adipocyte line 3T3-L1, knockdown of p53 had no effect on insulin-stimulated glucose uptake. There were no differences in Glut 1 or Glut 2 expression in the plasma membrane fraction or in the levels of phosphorylated AKT in cell lysates between primary hepatocytes transfected with p53 siRNA or control siRNA. Glycemic responses to insulin tolerance, glucose tolerance, and pyruvate tolerance tests did not differ between p53 knockout and wild type mice. Discussion. Thus, inhibition of p53 has pleiotropic effects, inhibiting glucose uptake in the liver but having no effect on adipocytes. Knockout of p53 has no apparent effect on glucose homeostasis in intact lean mice. An explanation for the association between p53 expression and hepatocyte glucose uptake remains to be elucidated.